EVALUATION OF CHEVALIER WG AND ATLANTIS OD HERBICIDES TO CONTROL WEEDS IN WINTER WHEAT FIELDS - & Jaff, Said (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
Herbicides are much more than just chemicals to control weed plants, and they can also influence the ecosystems. So, it is necessary to choose new herbicide with low active ingredients in order to reduce environmental issues, as well as control weed plants. A field experiment was conducted to evaluate the efficiency and to compare two herbicides containing similar active ingredients, Chevalier WG and Atlantis OD, as they contain metsufuron-methyl and iodosufuron-methyl sodium at different rates. Chevalier contains 30 g/l of each active ingredient; whilst Atlantis OD has 10 g/l of metsulfuron-methyl and 2 g/l of iodosufuron-methyl sodium. The results showed that all treatments significantly were active to control the weeds in both wheat varieties. Narrow-leaves Weeds density was decreased density 91.70 and 94.14% by Atlantis OD minus 25% in Aras and Simeto respectively, and the yield of Aras was increased 255%. In accordance with the results, a herbicide with low active ingredients, particularly from the sulfonylurea group such as Atlantis OD, more likely to be recommended for weed control and environmental concerns.